Message in a bottle [videorecording (DVD)] - Costner, Kevin; Mandoki, Luis; Newman, Paul, 1925-2008; Wright, Robin, 1966-; Savage, John, 1949-; Douglas, Illeana, 1965-; Coltrane, Robbie; Sparks, Nicholas (Warner Bros. Entertainment : Distributed by Warner Home Video, 2009)
An unforgettable film about a woman who stumbles upon a romantic letter stuffed inside a washed-up bottle, and who is at once determined to find the author, who ends up being a recently widowed shipbuilder.